Development of an income and cost simulation model for studio apartment using probabilistic estimation. Issue 5 (3rd September 2021) - Kim, Ji-Myong; Son, Kiyoung; Jang, Junho; Son, Seunghyun
ABSTRACT: The Korean construction industry has attracted interest and investment demand for lease-oriented investment products, such as shopping malls and studio apartments, as a substitute for financial products because of the low interest rates of the banks that resulted from the economic recession after the global financial crisis in 2008. However, there have been huge economic damages because of problems such as the oversupply, the increase in the unsold presale rate, and the decrease in rental profit. For studio-apartment development projects, dynamic analysis should be applied considering the correlation of variables in business analysis, which is complicated by such factors as profit structure and money flow. Therefore, we aim in this study to develop a statistical analysis model of studio apartments using probabilistic estimation. For this purpose, we developed a causal-loop diagram and established a simulation and optimization model. The developed model was verified by applying it to actual cases. Our results can be used as a reference for the optimization and risk management of studio-apartment business analysis in academia. In addition, from a practical point of view, this model can be used to develop a forecasting feasibility study based on risk and for business feasibility analysis. Graphical Abstract: uf0001